2022
DOI: 10.1097/psy.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of HIV With Mental Health in the Modern Antiretroviral Therapy Era

Abstract: People with HIV (PWH) receiving effective antiretroviral therapy (ART) continue to display residual immune dysregulation that amplifies the risk for neuropsychiatric comorbidities. At the same time, PWH commonly experience intersectional stigma and other psychosocial stressors that are linked to neuroendocrine stress responses, potentiate residual immune dysregulation, and alter other biobehavioral processes relevant to health outcomes. This special issue of Psychosomatic Medicine seeks to advance our understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“… 3 On the one hand, having a preexisting mental health disorder might be a contributory factor to contracting the virus, through engaging in risky behaviour such as injection drug use or engaging in risky sexual behaviour in those who have substance use disorders. 3 This increased risk of contracting HIV has been reported among individuals with substance use disorder, 9 while Wandel et al showed that the prevalence of substance use disorders was high in HIV positive persons even before the diagnosis of HIV. 10 Risky behaviour can also occur in those who are disinhibited in certain affective disorders like mania.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“… 3 On the one hand, having a preexisting mental health disorder might be a contributory factor to contracting the virus, through engaging in risky behaviour such as injection drug use or engaging in risky sexual behaviour in those who have substance use disorders. 3 This increased risk of contracting HIV has been reported among individuals with substance use disorder, 9 while Wandel et al showed that the prevalence of substance use disorders was high in HIV positive persons even before the diagnosis of HIV. 10 Risky behaviour can also occur in those who are disinhibited in certain affective disorders like mania.…”
Section: Introductionmentioning
confidence: 91%
“…They potentiate residual immune dysregulation and alter other biobehavioural processes relevant to health outcomes. 9 Suicide ideation is also common among PLWHA and it is very important to do a risk assessment. 2 A systematic review and meta-regression analysis by Tsai et al revealed a pooled prevalence estimate of suicidal ideation, attempted suicide and deaths by suicide of 22.3%, 9.6% and 1.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the widespread promotion of antiretroviral therapy (ART), a large percentage of patients living with HIV (PLWH) have a lifespan comparable to that of uninfected individuals ( Kirtane et al, 2018 ). Despite receiving effective ART, PLWH continue to be plagued by residual immune dysregulation, which increases their risk for neuropsychiatric comorbidities ( Carrico et al, 2022 ). Depression is one of the most common comorbidities among adult HIV-positive individuals, with prevalence of ~20–40% ( Pence et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%